2013
DOI: 10.1371/journal.pone.0056167
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Abrasiveness Is Associated with Variability of Microwear and Dental Surface Texture in Rabbits

Abstract: Dental microwear and 3D surface texture analyses are useful in reconstructing herbivore diets, with scratches usually interpreted as indicators of grass dominated diets and pits as indicators of browse. We conducted feeding experiments with four groups of rabbits (Oryctolagus cuniculus) each fed a different uniform, pelleted diet (lucerne, lucerne & oats, grass & oats, grass). The lowest silica content was measured in the lucerne and the highest in the grass diet. After 25 weeks of exposure to the diets, denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
125
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 50 publications
3
125
1
4
Order By: Relevance
“…The few previous studies have not focused on frugivory and granivory but on diet abrasiveness with a 32‐rabbit model (Schulz et al. 2013) and the phytolith/dust debate with a 4‐ewe model (Hoffman et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The few previous studies have not focused on frugivory and granivory but on diet abrasiveness with a 32‐rabbit model (Schulz et al. 2013) and the phytolith/dust debate with a 4‐ewe model (Hoffman et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies examining the effects of biogenic and abiotic abrasives have cast doubt on the central role of biogenic silica in scratch accumulation (Covert and Kay, 1981;Kay and Covert, 1983;Maas, 1991Maas, , 1994Gügel et al, 2001;Mainland, 2003;Sanson et al, 2007;Lucas et al, 2013;Schulz et al, 2013;Müller et al, 2014). Whereas an early study of material properties showed phytoliths were harder than sheep tooth enamel (Baker et al, 1959), subsequent nanoindentation tests have found phytoliths from four globally widespread species of grass to be softer than enamel (Sanson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, rabbits (Oryctolagus cuniculus) fed grass diets of increasing biogenic abrasiveness (i.e. higher phytolith content) showed higher relative scratch counts, greater variability among individuals (Schulz et al, 2013) and increased rates of tooth wear (Müller et al, 2014). Tooth wear rates also increased when rabbits were fed diets with abiotic abrasives (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Further, experimental studies have demonstrated different microwear attribute values in the same species when fed foods with different textural properties and/or grit loads (e.g. Schulz et al, 2013; Merceron et al, 2016). In many cases, the diets of extinct taxa are also vastly different from those of extant taxa, despite being members of the same family (e.g.…”
mentioning
confidence: 99%